PHYSICAL ILLNESSES AMONG ELDERLY PSYCHIATRIC OUT-PATIENTS WITH DEPRESSION - Sagar, Ratakonda S. (Medknow Publications, 1992)
Forty elderly psychiatric out-patients with an ICD-9 diagnosis of depression and twenty matched controls were studied for the presence of physical illnesses, using a pre-defined battery of investigative techniques. While the prevalence of physical illness diagnosis was not significantly different between the two groups, the number of subjects with undiagnosed illnesses and those with multiple illnesses was significantly higher among the depressives. Among specific illnesses, hypertension, osteoarthritis and cataract were significantly more common among depressives. Significance of the findings is discussed.